ANALYSIS OF THE INTERACTIONS OF NEURONAL APOPTOSIS GENES IN THE ASSOCIATIVE GENE NETWORK OF PARKINSON’S DISEASE - M. A. Yankina; O. V. Saik; P. S. Demenkov; E. K. Khusnutdinova; E. I. Rogaev; I. N. Lavrik; V. А. Ivanisenko (Вавиловский журнал генетики и селекции, 2018)
Parkinson’s disease (PD) affects an estimated 7–10 million people worldwide and 210000 people in Russia. PD is accompanied by degeneration of dopaminergic neurons and because of that neuronal apoptosis is an important factor in this disease. Analysis of gene networks is one of the key approaches in systems biology. We previously developed the ANDSystem tool, designed to automatically extract knowledge from scientific publications and reconstruct on this basis associative gene networks describing the molecular genetic mechanisms of biological processes. The aim of this work was prioritization of neuronal apoptosis genes by their involvement in PD pathogenesis, taking into account the structure of the PD associative gene network using ANDSystem. Analysis of the centrality of neuronal apoptosis genes, associated with PD, revealed that mean values of degree, closeness and betweenness centralities statistically significantly exceed such values of all nodes of the PD network. The APOE, CASP3 and GAPDH genes involved in neuronal apoptosis were among the most central genes. Prioritization of neuronal apoptosis genes for which there was no data in ANDSystem on their associations with PD was performed using standard methods (Endeavor and ToppGene) and the criteria of centrality and specificity of genes interactions with the PD gene network. Analysis revealed that genes involved in such processes as positive and negative regulation of neu ronal apoptosis, MAPK and ephrin receptor signaling pathways, are mainly represented among candidate genes with the highest priority (top 50, 70, 100 genes were considered). In particular, TP53, JUN, BCL2, PIK3CA and APP were among candidate genes with the highest priority.